Effect of fluvoxamine on plasma interleukin-6 in patients with major depressive disorder: a prospective follow-up study - Li, Xueqin; Yan, Danfeng; Liao, Mei; Zhang, Li; Li, ZeXuan; Liu, Bangshan; Chen, Yanjun; Zhang, Yan; Liu, Jin; Li, LingJiang (Frontiers in Psychiatry, 2023)
Introduction: Major depressive disorder (MDD) is associated with low-grade inflammation, and anti-inflammatory treatment can help improve depressive symptoms. A recent study found that fluvoxamine (FLV) can reduce Interleukin-6 (IL-6) production via sigma-1 receptor in inflammation models. However, the anti-il-6 effect of FLV in treating MDD patients and whether it can contribute to antidepressant effects remain unclear. Methods: A total of 65 MDD patients and 34 healthy controls were recruited at baseline, and 50 patients completed the FLV treatment for two months. We assessed depression and anhedonia and collected plasma IL-6 levels at baseline, one month, and two months after baseline. This study evaluated the changes in clinical measures and IL-6 during treatment and analyzed their association. Further subgroup analyses were conducted in MDD patients with higher, medium, or lower IL-6. Results: Depression and anhedonia were significantly improved in MDD patients, while the IL-6 did not significantly change after the FLV treatment. However, IL-6 significantly declined after the FLV treatment among MDD patients with higher baseline IL-6. No significant associations were found between the changes in depressive symptoms and IL-6. Conclusion: Our study provided preliminary evidence suggesting that the anti-IL-6 effect of FLV might not play a vital role in its antidepressant treatment, at least in MDD patients with low inflammation. However, for MDD patients with higher IL-6, FLV can help reduce IL-6 significantly in the antidepressant treatment, which may help guide the individual treatment of MDD with higher IL-6 levels.